NINJA-associated ERF19 negatively regulates Arabidopsis pattern-triggered immunity. (21st November 2018) - Huang, Pin-Yao; Zhang, Jingsong; Jiang, Beier; Chan, Ching; Yu, Jhong-He; Lu, Yu-Pin; Chung, KwiMi; Zimmerli, Laurent
Abstract : Phenotypic analyses of a new ethylene response factor, ERF19, involved in the negative regulation o f Arabidopsis pattern-triggered immunity. Abstract: Recognition of microbe-associated molecular patterns (MAMPs) derived from invading pathogens by plant pattern recognition receptors (PRRs) initiates a subset of defense responses known as pattern-triggered immunity (PTI). Transcription factors (TFs) orchestrate the onset of PTI through complex signaling networks. Here, we characterized the function of ERF19, a member of the Arabidopsis thaliana ethylene response factor (ERF) family. ERF19 was found to act as a negative regulator of PTI against Botrytis cinerea and Pseudomonas syringae . Notably, overexpression of ERF19 increased plant susceptibility to these pathogens and repressed MAMP-induced PTI outputs. In contrast, expression of the chimeric dominant repressor ERF19–SRDX boosted PTI activation, conferred increased resistance to the fungus B. cinerea, and enhanced elf18-triggered immunity against bacteria. Consistent with a negative role for ERF19 in PTI, MAMP-mediated growth inhibition was weakened or augmented in lines overexpressing ERF19 or expressing ERF19–SRDX, respectively. Using biochemical and genetic approaches, we show that the transcriptional co-repressor Novel INteractor of JAZ (NINJA) associates with and represses the function of ERF19. Our work reveals ERF19 as a novel player in the mitigation of PTI, and highlights a potential role for NINJA in fine-tuning ERF19-mediated regulation of Arabidopsis innate immunity.